The Impact of COVID-19 Lockdown in Banks and Financial Institutions' Stock Performance: Evidence from Nepal - Giri, Rajiv (Zenodo, 2021)
This paper examines the impact of COVID-19 lockdown on daily stock returns of banks and financial institutions (BFI) in Nepal. Employing the panel data regression models, this study examines the effect of daily COVID-19 positive cases to the stock returns – during pre-lockdown, lockdown, and after-lockdown period – of 74 listed firms in Nepal from 2 May 2019 to 25 April 2021. The empirical results confirm that there was no significant impact of daily increased number of COVID-19 positive cases to the stock returns of BFIs in Nepal throughout the entire study period. Furthermore, this study inquires the influence of pandemic period to the individual class of the BFIs sector in NEPSE. It discloses that the commercial banks, development banks and microfinance companies’ stock returns were adversely impacted during the pre-lockdown and lockdown period. However, after-lockdown period had significantly rebounded the overall BFIs stock returns in Nepal with the highest returns earned by microfinance companies and lowest return by commercial banks. Nepal Stock Exchange Limited : {"references": ["Al-Awadhi, A. M., Alsaifi, K., Al-Awadhi, A., & Alhammadi, S. (2020). Death and contagious infectious diseases: Impact of the COVID-19 virus on stock market returns. Journal of Behavioral and Experimental Finance, 27(May), 100326. https://doi.org/10.1016/j.jbef.2020.100326", "Alfaro, L., Chari, A., Greenland, A., & Schott, P. (2020). Aggregate and Firm-Level Stock Returns During Pandemics. SSRN Electronic Journal. https://doi.org/ 10.2139/ssrn.3562034", "Anh, D. L. T., & Gan, C. (2020). The impact of the COVID-19 lockdown on stock market performance: evidence from Vietnam. Journal of Economic Studies. https://doi.org/ 10.1108/JES-06-2020-0312", "Ashraf, B. N. (2020). Stock markets' reaction to COVID-19: Cases or fatalities? Research in International Business and Finance, 54, 101249. https://doi.org/10.1016/j.ribaf. 2020.101249", "Baig, A., Butt, H. A., Haroon, O., & Rizvi, S. A. R. (2020). Deaths, Panic, Lockdowns and US Equity Markets: The Case of COVID-19 Pandemic. SSRN Electronic Journal. https://doi.org/10.2139/ssrn.3584947", "Bash, A., & Alsaifi, K. (2019). Fear from uncertainty: An event study of Khashoggi and stock market returns. Journal of Behavioral and Experimental Finance, 23(October 2018), 54\u201358. https://doi.org/10.1016/j.jbef.2019.05.004", "Bell, A., & Jones, K. (2015). Explaining Fixed Effects: Random Effects Modeling of Time-Series Cross-Sectional and Panel Data. Political Science Research and Methods, 3(1), 133\u2013153. https://doi.org/10.1017/psrm.2014.7", "Bhusal, R. (2020). Order Management System User Manual Internet Based Fully Automated Online Trading System. Trade Management System User Manual.", "Buhagiar, R., Cortis, D., & Newall, P. W. S. (2018). Why do some soccer bettors lose more money than others? Journal of Behavioral and Experimental Finance, 18, 85\u201393. https://doi.org/10.1016/j.jbef.2018.01.010", "Chen, M. H., Jang, S. C. (Shawn), & Kim, W. G. (2007). The impact of the SARS outbreak on Taiwanese hotel stock performance: An event-study approach. International Journal of Hospitality Management, 26(1), 200\u2013212. https://doi.org/10.1016/j.ijhm.2005.11.004", "Chudik, A., Mohaddes, K., Pesaran, M. H., Raissi, M., & Rebucci, A. (2020). Economic consequences of Covid-19: A multi-country analysis | VOX, CEPR Policy Portal. October 19, 2020. https://voxeu.org/article/economic-consequences-covid-19-multi-country-analysis", "Chun-Da Chen, Chin-Chun Chen, Wan-Wei Tang, & Bor-Yi Huang. (2009). The Positive and Negative Impacts of the Sars Outbreak: A Case of the Taiwan Industries. The Journal of Developing Areas, 43(1), 281\u2013293. https://doi.org/10.1353/jda.0.0041", "Eleftheriou, K., & Patsoulis, P. (2020). COVID-19 Lockdown Intensity and Stock Market Returns: A Spatial Econometrics Approach. Munich Personal RePEc Archive, May, 1\u20139. https://mpra.ub.uni-muenchen.de/100662/", "Erin Schumaker. (2020). Timeline: How coronavirus got started. ABC News. https://abcnews.go.com/Health/timeline-coronavirus-started/story?id=69435165", "Fitria. (2013). Econometric Analysis of Panel Data. In Journal of Chemical Information and Modeling (Vol. 53, Issue 9).", "Goodell, J. W. (2020). COVID-19 and finance: Agendas for future research. Finance Research Letters, 35(March). https://doi.org/10.1016/j.frl.2020.101512", "Govenrment of Nepal. (2002). Nepal Rastra Bank Act, 2002 (Vol. 2058, Issue 2002). https://www.nrb.org.np/contents/uploads/2020/01/nepal_rastra_bank_act_2002_english.pdf", "He, Q., Liu, J., Wang, S., & Yu, J. (2020). The impact of COVID-19 on stock markets. Economic and Political Studies, 0(0), 275\u2013288. https://doi.org/10.1080/20954816.2020.1757570", "Ichev, R., & Marin\u010d, M. (2018). Stock prices and geographic proximity of information: Evidence from the Ebola outbreak. International Review of Financial Analysis, 56, 153\u2013166. https://doi.org/10.1016/j.irfa.2017.12.004", "Iqbal, B. A., & Sami, S. (2017). Papel de los bancos en la inclusi\u00f3n financiera en la India. Contaduria y Administracion, 62(2), 644\u2013656. https://doi.org/10.1016/j.cya.2017.0 1.007", "Jiang, Y., Zhang, Y., & Ma, C. (2017). H7N9 not only endanger human health but also hit stock marketing. Adv Dis Control Prev., 2(1), 1\u20137. https://doi.org/10.25196/ adcp 201711.H7N9", "Kowalewski, O., & \u015apiewanowski, P. (2020). Stock market response to potash mine disasters. Journal of Commodity Markets, 20(December 2019). https://doi.org/ 10.1016/ j.jcomm.2020.100124", "Ministry of Health and Population, G. of N. (2020). Coronavirus disease (COVID-19) outbreak updates & resource materials \u2013 Health Emergency Operation Center. In Ministry of Health and Population, Nepal. https://heoc.mohp.gov.np/update-on-novel-corona-virus-covid-19/", "Ministry of Law, J. and P. A. (2017). Bank and Financial Institution Act , 2073. In Government of Nepal (Vol. 2073, Issue 1).", "NEPSE. (2020). Nepal Stock Exchange Ltd. Nepal Stock Exchange Ltd. http://www.nepalstock.com/", "Nippani, S., & Washer, K. M. (2004). SARS: A non-event for affected countries' stock markets? Applied Financial Economics, 14(15), 1105\u20131110. https://doi.org/10. 1080/0960310042000310579", "Regmi, U. R. (2011). Stock Market Development and Economic Growth\u202f: Empirical Evidence from Nepal. Administration and Management Review, 24(1), 1\u201328.", "Shanaev, S., & Ghimire, B. (2019). Is all politics local? Regional political risk in Russia and the panel of stock returns. Journal of Behavioral and Experimental Finance, 21, 70\u201382. https://doi.org/10.1016/j.jbef.2018.11.002", "Shrestha, P. K. (2021). Impact of Covid-19 on Microfinance Institutions of Nepal NRB Working Paper No . 51 October 2020 Impact of Covid-19 on Microfinance Institutions of Nepal. Nepal Rastra Bank, 51(October 2020), 1\u201313.", "The Rising Nepal. (2020). NRB cuts interest rates by 2% for COVID affected businesses. The Rising Nepal. https://risingnepaldaily.com/business/nrb-cuts-interest-rates-by-2-for-covid-affected-businesses", "UNDP. (2020). COVID-19 pandemic | UNDP in Nepal. https://www.np.undp.org/ content/nepal/en/home/coronavirus.html", "WHO. (2020). Impact of COVID-19 on People's Livelihoods, Their Health and Our Food Systems. World Health Organization. https://www.who.int/news/item/13-10-2020-impact-of-covid-19-on-people's-livelihoods-their-health-and-our-food-systems", "WHO. (2021). WHO Coronavirus (COVID-19) Dashboard. WHO Coronavirus (COVID-19) Dashboard With Vaccination Data. WHO. https://covid19.who.int/", "World Health Organization (WHO). (n.d.). Statement on the second meeting of the International Health Regulations (2005) Emergency Committee regarding the outbreak of novel coronavirus (2019-nCoV). WHO. Retrieved June 1, 2021, from https://www.who.int/news/item/30-01-2020-statement-on-the-second-meeting-of-the-international-health-regulations-(2005)-emergency-committee-regarding-the-outbreak-of-novel-coronavirus-(2019-ncov)", "Zhang, D., Hu, M., & Ji, Q. (2020). Financial markets under the global pandemic of COVID-19. Finance Research Letters, 36(March), 101528. https://doi.org/ 10.1016/j.frl.2020.101528"]}